Performance study of heat-pipe solar photovoltaic/thermal heat pump system. (15th March 2017) - Chen, Hongbing; Zhang, Lei; Jie, Pengfei; Xiong, Yaxuan; Xu, Peng; Zhai, Huixing
Highlights: The testing device of HPS PV/T heat pump system was established by a finished product of PV panel. A detailed mathematical model of heat pump was established to investigate the performance of each component. The dynamic and static method was combined to solve the mathematical model of HPS PV/T heat pump system. The HPS PV/T heat pump system was optimized by the mathematical model. The influence of six factors on the performance of HPS PV/T heat pump system was analyzed. Abstract: A heat-pipe solar (HPS) photovoltaic/thermal (PV/T) heat pump system, combining HPS PV/T collector with heat pump, is proposed in this paper. The HPS PV/T collector integrates heat pipes with PV panel, which can simultaneously generate electricity and thermal energy. The extracted heat from HPS PV/T collector can be used by heat pump, and then the photoelectric conversion efficiency is substantially improved because of the low temperature of PV cells. A mathematical model of the system is established in this paper. The model consists of a dynamic distributed parameter model of the HPS PV/T collection system and a quasi-steady state distributed parameter model of the heat pump. The mathematical model is validated by testing data, and the dynamic performance of the HPS PV/T heat pump system is discussed based on the validated model. Using the mathematical model, a reasonable accuracy in predicting the system's dynamic performance with a relative error within ±15.0% can be obtained. The capacity of heat pump and the number of HPS collectors are optimized to improve the system performance based on the mathematical model. Six working modes are proposed and discussed to investigate the effect of solar radiation, ambient temperature, supply water temperature in condenser, PV packing factor, heat pipe pitch and PV backboard absorptivity on system performance by the validated model. It is found that the increase of solar radiation, ambient temperature and PV backboard absorptivity leads to the increase of the coefficient of performance based on thermal ( COPth ) of HPS PV/T heat pump system, while the increase of supply water temperature in condenser, PV packing factor and heat pipe pitch leads to the decrease of COPth . Furthermore, the increase of solar radiation and packing factor leads to the increase of the advanced coefficient of performance based on both thermal and electrical performances ( COPPV / T ), while the COPPV / T decreases as the ambient temperature, supply water temperature in condenser and heat pipe pitch increase. The PV backboard absorptivity has little influence on the COPPV / T of HPS PV/T heat pump system.